Penataan Permukiman Kumuh Tepian Kanal di Kelurahan Pattingalloang Kecamatan Ujung Tanah Kota Makassar - Indah Amalliah Gobel; Mimi Arifin; Samsuddin Amin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Pattingalloang District is one of the settlement areas including very high building and population density, and even tend to be a slum area. There are several identificated issues presented in this study include building structure and environmental conditions which are not suitable. Facilities and infrastructure inadequate settlements and economic conditions that still need improvement. The purpose of this study is to determine the physical and non-physical characteristics of existing settlements in Pattingalloang District as well as the concept of arrangement in accordance with the characteristics of settlements in the area. This study included in the descriptive research with quantitative and qualitative benchmarks. The analytical methods used include spatial, quantitative, qualitative and comparative. The results show some physical conditions of settlements in Pattigalloang District are inadequate including building structure, infrastructure, social and economic conditions. One of the concepts that can be proposed is the concept of arrangement as an effort to increase the quality of living environment that can indirectly help foster economic improvement of society.